A Review of COVID-19 Mass Testing in the United Arab Emirates - Al-Hosani, Farida; Al-Mazrouei, Shereena; Al-Memari, Shammah; Al-Yafei, Zain; Paulo, Marília Silva; Koornneef, Erik (Frontiers in Public Health, 2021)
Appropriate diagnostic testing to identify persons infected with SARS-COV-2 is a vital part of a health system’s ability to control the global pandemic of COVID-19 disease. The primary purpose of this review is to provide an overview of the mass testing strategy implemented throughout the UAE and the overall impact it has made on containing and controlling the spread of the disease. This study describes the mass testing strategy and capacity of the UAE during the pandemic of the new coronavirus SARS-COV-2. The UAE has conducted 15 million polymerase chain reaction (PCR) tests to SARS-COV-2, as of 15 November 2020. The number of tests per day varied from 10,000 by the end of March to 120,000 tests per day in November 2020. The mass testing initiative across the entire UAE forms an integral part of a bigger strategy focusing on testing, tracing con-tacts and isolating positive cases.